A novel human high-risk ependymoma stem cell model reveals the differentiation-inducing potential of the histone deacetylase inhibitor Vorinostat - Milde, Till; Kleber, Susanne; Korshunov, Andrey; Witt, Hendrik; Hielscher, Thomas; Koch, Philipp; Kopp, Hans-Georg; Jugold, Manfred; Deubzer, Hedwig E.; Oehme, Ina; Lodrini, Marco; Gröne, Hermann-Josef; et al. (Acta neuropathologica, 2011)
Incompletely resectable ependymomas are associated with poor prognosis despite intensive radio- and chemotherapy. Novel treatments have been difficult to develop due to the lack of appropriate models. Here, we report on the generation of a high-risk cytogenetic group 3 and molecular group C ependymoma model (DKFZ-EP1NS) which is based on primary ependymoma cells obtained from a patient with metastatic disease. This model displays stem cell features such as self-renewal capacity, differentiation capacity, and specific marker expression. In vivo transplantation showed high tumorigenic potential of these cells, and xenografts phenotypically recapitulated the original tumor in a niche-dependent manner. DKFZ-EP1NS cells harbor transcriptome plasticity, enabling a shift from a neural stem cell-like program towards a profile of primary ependymoma tumor upon in vivo transplantation. Serial transplantation of DKFZ-EP1NS cells from orthotopic xenografts yielded secondary tumors in half the time compared with the initial transplantation. The cells were resistant to temozolomide, vincristine, and cisplatin, but responded to histone deacetylase inhibitor (HDACi) treatment at therapeutically achievable concentrations. In vitro treatment of DKFZ-EP1NS cells with the HDACi Vorinostat induced neuronal differentiation associated with loss of stem cell-specific properties. In summary, this is the first ependymoma model of a cytogenetic group 3 and molecular subgroup C ependymoma based on a human cell line with stem cell-like properties, which we used to demonstrate the differentiation-inducing therapeutic potential of HDACi.
Gesehen am 19.08.2022